Present state and perspective development of the method of physical modulation of aircraft freely flying model - Горячих, А. И.; Кривцов, B. C.; Мелихов, П. В.; Смоляков, A. B.; Федорович, O. E.; Яшин, С. А. (Proceedings of National Aviation University (archive), 2000)
Considered is the present state and perspective development of physical modulation of the method of aircraft freely flying models, which are used as the instrument for complex investigation of dangerous effects and flight critical regime